New Functional Possibilities of Fire Detectors for Residential and Industrial Rooms - V. O. Kitikov; E. V. Ternov; A. V. Danilenko; N. I. Mukhurov; S. V. Denisyuk (Приборы и методы измерений)
The relevance of early detection of fire signs is quite obvious because due to the necessary measures for evacuating of people and material values, disconnecting the electrical equipment and extinguishing the fire at the time of the onset of fire or passive smoldering, human casualties can be completely avoided and economic losses can be minimized.A graphical representation of fire detectors' the classification in the form of a generalized scheme using all the main classification features, their advantages and disadvantages is given. The optimal areas for the use of detectors depending on the fire load are determined. The effectiveness of combined fire detectors' use, equipped in addition to traditional smoke and heat sensors with gas sensors, as an integrated approach to the organization of control over protected objects is shown.The results of development of highly sensitive two-zone sensor with sensitive elements based on iron oxide films for detecting the release of explosive and poisonous gases in the initial stage of decay before the formation of ignition conditions are presented. The use of gas sensors that respond to hazardous gases in the environment significantly reduces the risk of death due to carbon monoxide poisoning.